2013
DOI: 10.1155/2013/695179
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RKIP Inhibits Cell Invasion in Glioma Cell Lines through Upregulation of miR-98

Abstract: Raf-1 kinase inhibitor protein (RKIP) is a tumor and metastasis suppressor in cancer cells. MicroRNAs (miRNAs) have been suggested to play a vital role in tumor initiation and progression by negatively regulating oncogenes and tumor suppressors. Quite recently, studies have identified some miRNAs operating to promote or suppress tumor invasion or metastasis via regulating metastasis-related genes, providing potential therapeutic targets on antimetastasis strategy. In this study, we found that the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…79 Evidence from in vitro experiments using human glioma cell lines is consistent with a role of RKIP as a metastasis suppressor, since RKIP inhibition promotes cell migration, whereas its overexpression suppresses glioma cell invasion. 77,79 On the other hand, an in vivo assay using cultured human glioma cells implanted into chick chorioallantoic membrane did not find evidence for an effect of RKIP suppression on cellular proliferation and angiogenesis. 79 The cumulative evidence from this handful of studies supports a potential involvement of RKIP in human gliomas.…”
Section: Rkip and Association With Brain Cancermentioning
confidence: 90%
See 1 more Smart Citation
“…79 Evidence from in vitro experiments using human glioma cell lines is consistent with a role of RKIP as a metastasis suppressor, since RKIP inhibition promotes cell migration, whereas its overexpression suppresses glioma cell invasion. 77,79 On the other hand, an in vivo assay using cultured human glioma cells implanted into chick chorioallantoic membrane did not find evidence for an effect of RKIP suppression on cellular proliferation and angiogenesis. 79 The cumulative evidence from this handful of studies supports a potential involvement of RKIP in human gliomas.…”
Section: Rkip and Association With Brain Cancermentioning
confidence: 90%
“…76 An independent clinical study corroborated these findings in primary glioma tissues compared to adjacent normal glial tissues, and human glioma cell lines versus control human glial cells. 77 A third clinical study showed that overall survival was best for high-grade gliomas that are positive for RKIP and negative for STAT3 (signal transducer and activator of transcription 3) expression. 78 However, in another report, Martinho et al found that only a small proportion (i.e., approximately 10%) of gliomas from human patients are associated with loss of RKIP expression.…”
Section: Rkip and Association With Brain Cancermentioning
confidence: 99%
“…hsa-miR-98-5p belongs to the let-7 gene family and it is located at the Xp11.22 genomic locus (miRbase, HGNC site) [225]. Several studies have reported that miR-98 binds the 3 UTR of HMGA2 mRNA, regulating its expression [107][108][109][110][111][112]. A correlation between miR-98 and chemoresistance that is associated with the downregulation of HMGA2 was found in head and neck squamous cell carcinoma, providing the first link between miR-98 levels and HMGA2 expression [227].…”
Section: Hsa-mir-98mentioning
confidence: 99%
“…These studies gave a possible link between PEBP1/miR-98 and HMGA2 and revealed that upregulated PEBP1 in glioma cells leads to decreased tumour invasion without decrease in the cell proliferation rate. 38 PEBP1 also inhibits cell invasion mechanisms through induction of miR-200b, which in turn inhibits the expression of lysyl oxidase and Syndecan-2 in tumours, thereby inducing apoptosis in such cells and abrogating metastasis. 39 Hence, it is possible that PEBP1 plays a major role in cell invasion and metastasis by exerting its effects on the regulation of miRNAs in the human cells.…”
Section: Regulation Of Pebp1 By Mirnamentioning
confidence: 99%